ASSOCIATION BETWEEN BODY COMPOSITION AND FAT INFILTRATION IN THE LUMBAR MULTIFIDUS IN YOUNG ADULTS - Motta,Márcia Heloyse Alves (2020)
ABSTRACT Introduction: The increase in body fat is a natural and progressive process with aging, allowing fat infiltration in ectopic sites, such as skeletal muscle, which disrupts its function. Objective: To evaluate the association between body composition, fat infiltration into the low back multifidus muscles, and history of low back pain. Methods: This is a transversal and qualitative study that included young adult subjects of both sexes, and excluded individuals with neurological and musculoskeletal disorders and pregnant women. Fat infiltration into the multifidus and cross section area by magnetic resonance imaging; body composition by Dual-energy X-ray absorptiometry (DXA), and physical activity level determined by the International Physical Activity Questionnaire (IPAQ) were evaluated. The sample was divided by sex and. Pearson and Spearman's correlation and stepwise linear regression were performed. For this study, a p<0.05, a level of significance of 5% and confidence interval of 95% were adopted. Results: Thirty-two individuals were evaluated (59.37% women; 40.63% men). There was a correlation between fat percentage and total cross-sectional area (CSAtotal) (r=0.525; p=0.021), in women, and with lean abdominal mass (r= −0.648; p=0.017) and Body Mass Index (BMI) (r= −0.644; p=0.018) in men. There was also an association, in women, between fat percentage and cross section area (R2=0.275; p=0.021; CI=0.364 − 3.925) and, in men, with lean abdominal mass (R2=0.420; p=0.017; CI: −9.981- [-1.235]). Conclusion: There was correlation between fat percentage in the multifidus and CSA in women, and lean abdominal mass and BMI in men. There was also an association between fat percentage and cross section area in women, and lean abdominal mass in men. However, there was no evidence of any correlation between pain and low back dysfunction. Level of evidence I; Diagnostic studies - Investigating a diagnostic test.